Abundance and diversity of diatoms and dinoflagellates in an embayment off Central Chile (30°S): evidence of an optimal environmental window driven by low and high frequency winds - Jacob, Barbara Gianella; Astudillo, Orlando; Dewitte, Boris; Valladares, María; Alvarez Vergara, Gonzalo; Medel, Carolina; Crawford, David W.; Uribe, Eduardo; Yanicelli, Beatriz (Frontiers in Marine Science, 2024)
The relationship between phytoplankton abundances and wind forcing in upwelling systems involves a number of processes that make the relationship nonlinear in nature. In particular, although upwelling-favorable winds tend to provide nutrients for phytoplankton growth, they can also induce export of both biomass and nutrients to the open ocean through Ekman and eddy-induced transport, or dilution of populations through vertical mixing, which negatively impacts increase in biomass. These processes are essentially nonlinear and can interact antagonistically or synergistically on the overall coastal accumulation of biomass. Consequently, producers and consumers tend to decline above a certain wind threshold despite input of nutrient-enriched water. We have observed this phenomenon in an embayment off Central Chile (30°S), where almost 10 years (2000-2009) of microphytoplankton data were analyzed together with environmental variables and wind phenology. Our findings showed that abundance, species diversity and evenness of diatoms and dinoflagellates all increased post-2005 when the mean of the alongshore surface wind stress reached a maximum threshold value of 0.026 N m-2, observed at the decadal temporal variability scale. The increased abundances of diatoms and dinoflagellates post-2005 was associated with the changing phase of the Pacific Decadal Oscillation (PDO) from positive (warm) to negative (cold) phases, which was also associated with a decrease in the intra-seasonal wind activity. Both abundance and diversity of the microphytoplankton community peaked during the post-2005 period whereas higher abundances and frequency of harmful algal blooms (e.g. Pseudo-nitzschia australis) were observed prior to 2005. We suggest that the low-frequency (decadal) variations of mean wind stress during a transition phase of the PDO combined with the reduction in intra-seasonal (periods shorter than 2 months) wind variability after 2005 provided an “optimal environmental window” for the ecosystem.